The Effect of Internationalising the Student Community on Graduate Students' Global Citizenship:: A case from Uganda - Ayebare, Justine (International Journal of African Higher Education, 2021)
This article examines the effect of internationalising the student community on graduate students’ demonstrated commitment to global citizenship at a university in Uganda. It arose from a sequential explanatory survey study. Quantitative and qualitative data were gathered from a sample of 180 graduate students, with the former analysed employing descriptive and inferential statistics, while the latter were analysed using thematic content analysis. The quantitative results revealed that an internationalised student community has a statistically significant positive effect on graduate students’ demonstrated global competence, but not on their demonstrated commitment to social responsibility. The qualitative findings produced similar results. They revealed that the presence of international students on campus coupled with graduate students’ participation in international activities such as conferences and inter-cultural activities promoted their commitment to global citizenship. These findings are in line with those of previous studies. We thus recommend that universities in Uganda and other developing countries in the Global South further internationalise their graduate student community as a strategy to promote their commitment to global citizenship. Key words: internationalisation, global citizenship, globalisation, higher education, student community